Flood Inundation Mapping Using Synthetic Aperture Radar Data Single Polarization: A Case Study of Flood in Lake Tempe, South Sulawesi-Indonesia. Issue 1 (September 2020) - Febrianti, N; Yulianto, F; Arda, M; Haryani, N
Abstract: Remote sensing data can be used to help disaster management and environmental management because this data has advantages in terms of speed, is more efficient, can reach large and remote areas. Aside from that, it has consistency in measurement, can make repeated measurements, and has measurable accuracy. Floods in Lake Tempe occur almost every year due to overflowing of Lake Tempe. This research will detect flood inundation from Sentinel-1 data with single-polarization of flooding in Lake Tempe, South Sulawesi. The data used were Sentinel-1 data before flooding (2 May 2018) and after flooding (26 May 2018). The Single polarization of the Sentinel-1 can be used very well to identify floods event. The difference of input band uses the threshold of -6, and enables smoothing of 10. Utilization of tidal junction between Lake Tempe and Lake Sidenreng for agriculture and settlement has caused flooding due to lake water overflowing in the rainy season. This single polarization method can already be used in flooded areas, although in some locations it is still overestimates.